Fukushima and beyond nuclear power in a low-carbon world - Hubbard, Christopher (Ashgate Pub., 2014)
In light of the Fukushima-Daiichi nuclear accident of 2011 the prospect of including or excluding nuclear power in a low-carbon twenty-first century world is now increasingly critical. It is in this emerging scenario and context that this book presents a full suite of historical, contemporary and projected data.